The Influence of Product Quality on Customer Loyalty at Diagram Coffee Bandung in 2025 - Nurzahra Sugiharti; Leni Cahyani (Green Publisher Indonesia, 2025)
The global and national coffee industry has experienced rapid growth in recent years, including in Indonesia, which is one of the major coffee producers and consumers in the world. The city of Bandung as the center of coffee shop business growth presents intense competition between business actors, so product quality is an important factor in maintaining customer loyalty. This study aims to analyze the effect of product quality on customer loyalty at Diagram Coffee Bandung. The research uses a quantitative approach with descriptive methods, which involves collecting data through questionnaires to Diagram Coffee customers. Data analysis was performed statistically to measure the relationship between product quality variables and customer loyalty. The results showed that product quality which includes taste, consistency, and presentation aesthetics has a positive and significant influence on customer loyalty. This finding confirms that product quality plays an important role in driving repeat purchases and customer recommendations for Diagram Coffee. This research contributes to the development of coffee shop business strategies in improving product quality as an effort to retain customers in the midst of increasingly fierce industry competition.